Tunable magnetic skyrmions in spintronic nanostructures for cellular-level magnetic neurostimulation. (2nd September 2019) - Saha, Renata; Wu, Kai; Su, Diqing; Wang, Jian-Ping
Abstract: Electrical probes and arrays are currently ruling the market in treating neurodegenerative, sensory and cardiovascular diseases. Despite the accomplishments, their performance is limited by high power of operation, tissue inflammation, biofouling, inefficient control of electric fields and significant incompatibility for patients who are qualified to take magnetic resonance imaging tests only. Another alternative is magnetic stimulation. In this paper, we have proposed an implantable, highly tunable skyrmion-based neurostimulator (SkyNS). The displacement of magnetic skyrmions in a metallic bilayer generates a time varying magnetic field which induces an electric field gradient large enough to trigger neuron stimulation. SkyNS operates with a current of 2.71 µ A and consumes a power of 1.434 nW. The effects of Dzyaloshinskii–Moriya interaction, perpendicular magnetic anisotropy and device dimensions on stable skyrmion nucleation and smooth skyrmion dynamics in a heavy metal/ferromagnetic metal bilayer have been extensively studied by micromagnetic simulation on mumax3. This work provides a proof-of-concept to exploit the material tunability of skyrmion-based spintronic nanodevices as cellular-level, ultra-low power, implantable magnetic neurostimulators.